Pengaruh Proses Pengeringan terhadap Aktivitas Antioksidan Dari Wortel (Daucus carota L.): Sebuah Ulasan - Rifqi, Muhammad; Faridah, Faridah; Triandita, Nanda (Jurnal Riset, Inovasi, Teknologi & Terapan, 2025)
Carrots are a horticultural commodity rich in beta-carotene and antioxidants, but have the major disadvantage of a short shelf life due to their high moisture content. This study evaluated the effect of three drying methods, such as sun drying, oven drying, and freeze drying, on the reduction of moisture content, shelf life, and stability of carrot bioactive compounds. Each method was applied until uniform final moisture content was achieved, and then changes in antioxidant activity and beta-carotene content were analyzed. The results showed that all methods were able to reduce the moisture content and extend the shelf life of carrots. However, sun and oven drying caused significant decreases in beta-carotene and antioxidant activity. In contrast, freeze-drying gave more optimal results with minimal nutrient degradation. Therefore, freeze-drying is recommended as the best method to maintain the functional quality of dried carrots while extending their shelf life.